Internalization of Islamic Values at Sekolah Indonesia Jeddah: Synergy of Curriculum and Technology in Learning - Amalia, Novi Rizka; Suryadarma, Yoke; Maulida, Savira; Chaidir, Ahmad (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
The rapid advancement of digital technology presents new opportunities for enhancing religious education while addressing challenges in preserving Islamic values in a globalized world. This community engagement program at Sekolah Indonesia Jeddah focuses on the internalization of Islamic values through the synergy of curriculum and digital technology. Conducted in collaboration with the school, the program integrates participatory methods to align with the institution's educational objectives. The key initiatives include incorporating digital tools into religious education, enhancing educators' digital literacy, and fostering interactive and immersive learning experiences that reinforce Islamic teachings. Initial findings indicate an increased awareness and deeper understanding of Islamic principles among students, alongside improved engagement in digital-based religious activities. This initiative serves as a model for leveraging technology in faith-based education within multicultural and transnational academic environments, ensuring that spiritual values remain integral to students' holistic development.